(untitled) (RT. A Journal on Research Policy and Evaluation, 2017)
The Italian university, after the birth of the Republic, continued for many years to be characterized by a marked centralism, despite the wide autonomy recognized by the Art. 33 of the Italian Constitution. Since the last eighties a progressively increased autonomy has been granted, initially only statutory and then also regulatory, financial, didactic and in recruiting, which provided the universities with the tools to move quickly towards the European and international competition. However, starting from the financial crisis in 2008, all the governments have chosen to dramatically change the course by starting a path of downsizing the university system, with a gradual subtraction of financial resources into the universities and a parallel limitation of autonomy. The impact of the policies adopted has been a disaster and has pushed Italy into the last positions among the European Union countries for funding at universities and last place by number of graduates in the age range of 30-34 years. In line with this approach is also framed the law of December 30, 2010, no. 240, the so-called Gelmini Law, with which a radical reversal of the system has been settled with respect to the previous autonomy policies on the university. The substantial carelessness towards the university, when not the hostility, shown by the policy and the widespread idea that its funding is not seen as an investment, but rather as an expense and a luxury that we cannot afford, leaves little hope for the future of our country and lets us imagine more and more obscure scenarios. Political choices, whether deliberately or not, are progressively leading to the dismantling of the Italian university.